Perinatal Palliative Care: Barriers and Attitudes of Neonatologists and Nurses in Poland. (28th October 2013) - Korzeniewska-Eksterowicz, Aleksandra; Respondek-Liberska, Maria; Przysło, Łukasz; Fendler, Wojciech; Młynarski, Wojciech; Gulczyńska, Ewa
Abstract : Objective . To identify barriers and personnel attitudes towards realization of palliative care principles in neonatological units. Study Design . An anonymous questionnaire was posted to all heads of departments and head nurses of all the 27 neonatological units in the Lodz area. Results . We received 46 (85%) questionnaires. Final analysis comprised 42 properly filled-in questionnaires (by 22 doctors and 20 nurses). In case of prenatal diagnosis of a lethal defect, 77.27% of doctors and 65% of nurses opted for informing the mother also about the possibility of pregnancy continuation and organization of palliative care after delivery. Most of respondents accepted conditions for abortion pointed by the Polish law. The most common barriers pointed out by both groups were insufficient knowledge of the personnel on palliative medicine and family preference for life sustaining treatment. Conclusions . Understanding attitudes of personnel towards palliative care and identification of barriers are a starting point for future efforts to improve the system of neonatological care.